Establishing a school network from the perspective of the competences of the school superintendent – an analysis of legal solutions in the light of the recent reform of the educational system - Kurzyna-Chmiel, Danuta (The Opole Studies in Administration and Law, 2020)
The local schools authorities represented by chief education officers perform pedagogical supervision and control. They also cooperate with local government units which are responsible for realization of most of the educational tasks. The latest reform of the educational system has considerably broadened the superintendents’ competences in many aspects, for example as regards evaluation of schools networks. Undoubtedly, the competences of the school superintendent limit the independence of local self-governments as far as their deciding about schools is concerned. In essence, the problem concerns the creation of legal solutions that allow universal access to education. One should strive to create a network of schools, which will remain unchanged for many years. The network must ensure a sense of security in the implementation of educational benefits to residents.